Wealth and Executive Compensation - BECKER, BO (Journal of Finance, 2006)
ABSTRACT Using new data on the wealth of Swedish CEOs, I show that higher wealth CEOs receive stronger incentives. Since high wealth (excluding own‐firm holdings) implies low absolute risk aversion, this is consistent with a risk aversion explanation. To examine whether wealth is likely to proxy for power, I use lagged wealth (typically measured before the CEO was hired), and the results remain for one of two incentive measures. Also, the wealth–incentive result is not stronger for CEOs likely to face limited owner oversight. Finally, wealth is unrelated to pay levels, and is hence unlikely to proxy for skill.